Esport expertise benefits perceptual-cognitive skill in (traditional) sport - Murphy, C. P.; Wakefield, A.; Birch, P. D. J.; North, J. S. (Journal of Expertise, 2021)
The ability to recognise patterns in developing sequences of play is a characteristic of experts that consistently distinguishes them from less-skilled performers. In addition to in situ training, researchers and practitioners seek alternative, simulated practice activities that may assist in the development of such perceptual-cognitive skills, whilst limiting physical load. In this study, we investigated whether pattern recognition skills of esport experts transferred to traditional sport. Expert esport (FIFA) players, skilled soccer players and a control group of novices in both FIFA and soccer completed two pattern recognition tasks, one that involved viewing and identifying previously seen footage of structured sequences from competitive FIFA 19 matches and another displaying sequences from soccer matches. Both skilled groups recognised previously viewed sequences significantly more accurately than the control group irrespective of viewing condition. Moreover, although expert FIFA players were more accurate than skilled soccer players in the FIFA 19 condition, no difference was observed between the two groups in the soccer condition. Positive transfer of pattern recognition skill was therefore stronger from FIFA to soccer than in the other direction. The findings suggest that engagement in esport may aid the development of perceptual-cognitive skills required for expert performance in traditional sport.